Inequality of Income Distribution in Rural and Urban Poor Communities (A Case Study on Former Beneficiaries of PNPM-M Program in Banyumas Regency) - Dijan Rahajuni; Suprapto Suprapto; Lilis Siti Badriah; Sri Lestari; Ascaryan Rafinda (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2017)
The success of economic development should not only focus on economic growth, but also efforts to increase income and purchasing power along with equal income distribution. Inequality of income distribution is a problem that must be addressed immediately because it will have a broad impact on the next development process. The object of this research was poor communities as the beneficiaries of revolving loan of The National Program for Community Empowerment-Independent (PNPM-M). The research method was survey on beneficiary respondents in urban areas (PNPM-MP) and rural areas (PNPM-PMd), conducted using a questionnaire. Data analysis in this research used income distribution inequality criteria from World Bank and Gini Ratio. The result found that more than 50% of respondents both in groups and areas had low income and did not meet the standard for decent living standard (KHL). The average respondents income distribution both in the groups or areas according to the World Bank and Gini Ratio criteria was in the moderate category. However according to areas, inequality of income distribution in rural areas was higher than in urban areas. To minimize income inequality between the communities, community groups and areas, it is necessary to empower the community based on the potential of local economic resources.Keywords: Income Distribution, PNPM-M, KHL, Gini Ratio